Apply L to both sides:
(s^2 Y(s) - 0s - 0) + 2Y(s) = 3 * 2/(s^2 + 2^2)
==> (s^2 + 2) Y(s) = 6/(s^2 + 4)
==> Y(s) = 6/[(s^2 + 2)(s^2 + 4)]
By partial fractions:
Y(s) = 3/(s^2 + 2) - 3/(s^2 + 4).
Inverting yields y(t) = (3/√2) sin(t√2) + (3/2) sin(2t).
--------------
P.S.: Via convolution, we have
y(t) = L⁻¹ {6/[(s^2 + 2)(s^2 + 4)]}
......= L⁻¹ {1/(s^2 + 2)} * L⁻¹ {6/(s^2 + 4)}
......= (1/√2) sin(t√2) * (6/2) sin(2t)
......= ∫(s = 0 to t) (1/√2) sin(s√2) · (6/2) sin(2(t - s)) ds, by definition of convolution (*)
......= ∫(s = 0 to t) (-3/√2) sin(s√2) sin(2s - 2t) ds
......= ∫(s = 0 to t) (-3/√2) (1/2) [cos(s√2 - (2s - 2t)) - cos(s√2 + (2s - 2t))] ds, trig. identity
......= (-3/(2√2)) [sin(s√2 - (2s - 2t))/(√2 - 2) - sin(s√2 + (2s - 2t))/(√2 + 2)] {for s = 0 to t}
......= (-3/(2√2)) [sin(t√2) (1/(√2 - 2) - 1/(√2 + 2)) - sin(2t) (1/(√2 - 2) + 1/(√2 + 2))]
......= (-3/(2√2)) [-2 sin(t√2) - √2 sin(2t)], via common denominators
......= (3/√2) sin(t√2) + (3/2) sin(2t).
I hope this helps!